Passive flow control valve for protein delivery. Issue 1 (1st January 2017) - Cornaggia, L.; Conti, L.; Hannebelle, M.; Gamper, S.; Dumont-Fillon, D.; van Lintel, H.; Renaud, P.; Chappel, E.
Abstract: Passive flow control valves are usually intended to deliver or drain a fluid at a constant rate independently of pressure variations. Microfluidic devices made of a stack of two plates are considered here: the first plate comprises a flexible silicon membrane having through holes while the second plate is a rigid substrate with a cavity, an outlet hole and pillars aligned with the through holes of the membrane. The liquid flows through the holes etched in the membrane and through the gap between the membrane and the pillars. Each gap can be considered as a valve which progressively closes as the pressure increases. Numerical modelling of the fluid dynamics inside the device associated with FEM simulations of the membrane distortion have been performed to design a device that exhibits a constant flow rate in a specified range of pressure. To make the design more reliable, the device characteristics have been optimized using a genetic algorithm, the fitness function taking notably into account machining and alignment tolerances. This algorithm has been finally used to design flow control valves for wearable injectors dedicated to the infusion of viscous drug formulations (hyaluronic acid, adalimumab, golimumab …) at high pressure. Prototypes have been characterized using solutions of 12 and 24 cP. It has been demonstrated experimentally that this technology is suitable to passively infuse biological products at flow rates up to 1 mL/min. The numerical model has then been refined further so as to obtain a good correlation with experimental data.